PENGARUH TATA KELOLA PERUSAHAAN TERHADAP KECURANGAN LAPORAN KEUANGAN PERUSAHAAN - Virsella, Vinny; Febyansyah, Andar (JURNAL LENTERA BISNIS, 2025)
This study aims to examine the effect of corporate governance on financial statement fraud. Several corporate governance indicators used in this study are board size, board international experience, audit committee expertise, and internal audit competency. The sampling technique used purposive sampling with several criteria. The total sample in this study was 180 data from 45 mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. This study used multiple linear regression and was processed using the SPSS 25 statistical testing application. The results showed that board size and internal audit competency had a positive impact on corporate fraud reports, while board international experience and audit committee expertise were not proven to have an influence on the occurrence of financial statement fraud